The JAK-Inhibitor Tofacitinib Rescues Human Intestinal Epithelial Cells and Colonoids from Cytokine-Induced Barrier Dysfunction. Issue 3 (21st November 2019) - Sayoc-Becerra, Anica; Krishnan, Moorthy; Fan, Shujun; Jimenez, Jossue; Hernandez, Rebecca; Gibson, Kyle; Preciado, Reyna; Butt, Grant; McCole, Declan F
Abstract : By conducting a series of fecal microbiota transplantation experiments, we show a variable effect on ileitis severity from human gut microbiota isolated from IBD donors in remission and that of healthy controls in a mouse model of IBD. Abstract: Background: Alterations to epithelial tight junctions can compromise the ability of the epithelium to act as a barrier between luminal contents and the underlying tissues, thereby increasing intestinal permeability, an early critical event in inflammatory bowel disease (IBD). Tofacitinib (Xeljanz), an orally administered pan-Janus kinase (JAK) inhibitor, was recently approved for the treatment of moderate to severe ulcerative colitis. Nevertheless, the effects of tofacitinib on intestinal epithelial cell functions are largely unknown. The aim of this study was to determine if JAK inhibition by tofacitinib can rescue cytokine-induced barrier dysfunction in intestinal epithelial cells (IECs). Methods: T84 IECs were used to evaluate the effects of tofacitinib on JAK-signal transducer and activator of transcription (STAT) activation, barrier permeability, and expression and localization of tight junction proteins. The impact of tofacitinib on claudin-2 promoter activity was assessed in HT-29 IECs. Tofacitinib rescue of barrier function was also tested in human colonic stem cell-derived organoids. Results: Pretreatment with tofacitinib prevented IFN-γ-induced decreases in transepithelial electrical resistance (TER) and increases in 4 kDa FITC-dextran permeability (FD4), partly due to claudin-2 transcriptional regulation and restriction of ZO-1 rearrangement at tight junctions. Although tofacitinib administered after IFN-γ challenge only partially normalized TER and claudin-2 levels, FD4 permeability and ZO-1 localization were fully recovered. The IFN-γ-induced FD4 permeability in primary human colonoids was fully rescued by tofacitinib. Conclusions: These data suggest differential therapeutic efficacy of tofacitinib in the rescue of pore vs leak-tight junction barrier defects and indicate a potential contribution of improved epithelial barrier function to the beneficial effects of tofacitinib in IBD patients.